1985
DOI: 10.1080/09553008514551301
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Platinum Drug Interaction

Abstract: Platinum drugs have chemical as well as biochemical and biological effects on cells, all of which may interact with radiation effects. They inhibit recovery from sublethal and potentially lethal radiation damage. They produce a pattern of chromosome aberrations analogous to that from alkylating agents. Cellular sensitivity to platinum is increased when glutathione levels are reduced, just as is radiosensitivity. There is a pattern of drug sensitivity throughout the phases of the cell cycle which is different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Cell cycle perturbations and reac¬ tions with nonprotein SH groups also occur with platinum radiosensitization. 47 Sublethal damage occurs with single-strand breaks that are repaired with DNA excision repair and after replica¬ tion repair processes.56"58 The gaps filled in by the replica¬ tion repair process may occur by recombination, de novo synthesis,59 or by passing the lesion via branch migra¬ tions.60 Postradiation cellular damage occurs by the inhi¬ bition of such recovery processes. Usually the repair of DNA single-stranded breaks are rapid with about 85% complete at 60 minutes after irradiation.17 Studies have shown the DNA repair processes after treatment with cisplatin to be significantly slower.61 Steric hinderance of platinum-bound DNA leads to misrepaired radiation lesions resulting in chromatid aberrations, possibly in a supra-additive manner.…”
Section: Al53 and Van Denmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle perturbations and reac¬ tions with nonprotein SH groups also occur with platinum radiosensitization. 47 Sublethal damage occurs with single-strand breaks that are repaired with DNA excision repair and after replica¬ tion repair processes.56"58 The gaps filled in by the replica¬ tion repair process may occur by recombination, de novo synthesis,59 or by passing the lesion via branch migra¬ tions.60 Postradiation cellular damage occurs by the inhi¬ bition of such recovery processes. Usually the repair of DNA single-stranded breaks are rapid with about 85% complete at 60 minutes after irradiation.17 Studies have shown the DNA repair processes after treatment with cisplatin to be significantly slower.61 Steric hinderance of platinum-bound DNA leads to misrepaired radiation lesions resulting in chromatid aberrations, possibly in a supra-additive manner.…”
Section: Al53 and Van Denmentioning
confidence: 99%
“…Usually the repair of DNA single-stranded breaks are rapid with about 85% complete at 60 minutes after irradiation.17 Studies have shown the DNA repair processes after treatment with cisplatin to be significantly slower.61 Steric hinderance of platinum-bound DNA leads to misrepaired radiation lesions resulting in chromatid aberrations, possibly in a supra-additive manner. 47 Of the 93 animals entered into this study, 71 (76%) sur¬ vived through the completion of the experiment on day 63. Anesthetic deaths occurred in eight (8.6%), while loss of the remaining 14 (14.4%) animals was attributed to any combination of stress and toxicity from surgery, radiation, or carbocisplatin.…”
Section: Al53 and Van Denmentioning
confidence: 99%
“…50, NO. 5, 945-946 Letter to the Editor Radiation and platinum drug interaction (Received 4 June 1986) In a review article entitled 'Radiation and platinum drug interaction' by Nias (1985), we were more than somewhat surprised to read an inaccurate citation of the details and misrepresentation of the significance of a case reported by us (Golding and van Zanten 1983).…”
mentioning
confidence: 99%
“…Radiation can enhance interstrand cross-linking by BCNU (Tofilon et al, 1984). Cross-linking agents have also been found to enhance radiation-induced cell killing in mammalian cells in vitro (Nias, 1985;Wheeler et al, 1977) and the combination can be more effective in vivo than the single agents (Barker et al, 1979;Walker & Gehan, 1976).…”
mentioning
confidence: 99%